Agriculture and wildlife in California's Central Valley: mutually exclusive or win-win? - Bias, Michael A., author; Payne, Jack M., author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 1996)
Because of the importance of California's Central Valley and private lands to waterfowl, Ducks Unlimited (DU) increased its conservation effort on private lands in 1990. This private land effort, delivered from DU's Western Regional Office in Sacramento, is known as Valley CARE (Conservation of Agriculture, Resources, and the Environment). Valley CARE emphasizes agricultural enhancement and wetland restoration and enhancement conservation efforts among the three geographically distinct areas of the Central Valley: the Sacramento Valley, the Sacramento-San Joaquin Delta (Delta), and the San Joaquin Valley. From surveys conducted by DU of water districts in the Sacramento Valley, during 1993-94, rice growers winter-flooded at least 90,000 acres (36,423 ha) of harvested rice fields; during 1994-95, winter-flooded rice acreages increased to over 140,000 (56,658 ha); and during 1995-96, at least 100,000 acres (40,470 ha) of harvested rice fields were winter-flooded. DU also works with farmers in the Delta to winter-flood harvested com and wheat for shorebirds, swans, geese, ducks, and other waterbirds. Cooperating landowners contributed nearly 17,000 flooded acres (6,880 ha) during 1994-95 and about 16,000 acres (6,475 ha) during 1995-% to over 30,000 acres (12,141 ha) that were flooded in the Delta during those years. The expected agronomic values and economic benefits of agricultural enhancement appear to be as high as expected and the biological values are substantial. Close to 30% of all waterbirds using rice fields are non-waterfowl species and half of these are shorebirds. DU also has expanded the Valley CARE effort in the Central Valley to establish a series of permanent wetland restorations and enhancements along with the agricultural systems. This mosaic landscape approach is fundamental to the ongoing management efforts for migratory waterbirds in California's Central Valley. This program's results demonstrate what can be accomplished when private conservation groups and agricultural organizations work together and with traditional government wildlife agencies for the mutual benefit of agriculture and conservation.
1996 USCID wetlands seminar
California's Central Valley
Not digitized by CSUL Digital Services.
Presented at Water for agriculture and wildlife and the environment: win-win opportunities: proceedings from the USCID wetlands seminar on June 27-29, 1996 in Bismarck, North Dakota.